Decision Support System Penilaian Kinerja Kepala Sekolah SD Kecamatan Pardasuka Kabupaten Pringsewu Menggunakan Metode Weighted Product - Anggara, Dian; Susilowati, Tri (JELTec (Journal of Learning Technology), 2024)
Principal performance assessment is an analysis process in order to produce good teaching. The process of assessing the performance of Elementary School Principals in Pardasuka District, Pringsewu Regency is not very detailed and still uses a manual system. This study aims to design a decision support system (DSS) in assessing the performance of principals in elementary schools in Pardasuka District, Pringsewu Regency, using the Weighted Product (WP) method. The WP method was chosen because of its ability to handle multi-dimensional criteria and provide different weights for each assessment criterion. Data were collected through questionnaires, interviews with related parties, observations and literature studies. This study used 7 criteria. The results of this system indicate that the assessment of principal performance can be carried out objectively and transparently, and facilitate decision making in developing the professionalism of principals. With this system, it is expected to improve the quality of education in Pardasuka District by improving the performance of principals. This study also recommends further development of the system to include more in-depth analysis and reporting features